Assessing the Economic Security of Ukraine Using the Construct Approach - Kozachenko Ganna V.; Pohorelov Yurii S.; Gerasymenko Larysa V. (Bìznes Inform, 2020)
Assessments of the economic security of the State along with other components (for example, resources) are the basis for its provision, which determines the relevance of the assessment of the security of the country’s economy. In assessing the economic security of the State, the starting position is to understand the content of this category, which provides an answer to the question of what constitutes the economic security of the State. Further operationalization of the constructs of the selected approach to the interpretation of the content of the category of «economic security of the State» directly lays the foundations of the methodical base of its assessment. The most common in assessing the economic security of the State is the functional approach, which provides for the allocation of a number of components of economic security of the State, which, as a rule, is not specified in the attributes of determining the category of «economic security of the State». According to the analysis of the application of the functional approach in the assessment of the economic security of the State, contradictory aspects have been found, which are caused by the inconsistency of the main directions of assessment of the constructs of the category of «economic security of the State» (as a rule, the main directions of evaluation coincide with the results of the functioning of the national economy system). In order to overcome the identified contradictory aspects, the definition of the category «economic security of the State», consisting of three constructs, is suggested; in each case 5-6 primary quantitative indicators are selected for the operationalization of them. The assessment of the economic security of the State used temporal form of indicators, which has several undoubted advantages, which, in particular, include the receipt of assessments of changes in the economic security of the State during the analyzed period. The operationalization of the proposed construct approach to the assessment of the economic security of the State allows to obtain a quantitative dynamic assessment for each of its constructs, which are adequate to (correspond to) the selected definition of the content of the category «economic security of the State». The proposed construct approach to assessing the economic security of the State and its operationalization allow to avoid the primary indicators, necessary in the use of functional approach of rationing of the different in nature and dimension, their multiple convolution, which inevitably affects the quality of assessments of economic security of the State, because to some extent distorts and impersonates them.